PEMBIASAAN PERILAKU SOPAN SANTUN DALAM UPAYA MENINGKATKAN KARAKTER ISLAMI SANTRI DI PONDOK PESANTREN - Makhmudah, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) STAI Nahdlatul Ulama (STAINU) Malang, 2025)
Islamic boarding schools are very important in playing a role in instilling good morals. And it is hoped that Islamic boarding schools will become a place of social reliability of morals that must be given to students. Although Islamic boarding schools are still lacking in instilling morals, therefore the program